Relationship Between 6-n-propylthiouracil (prop) Taster Status, Dietary Intake and Dental Caries Among Young Adult Subjects - Syathirah Hanim Azhar Hilmy; Ruhaya Hasan; Norkhafizah Saddki; Marina Abdul Manaf (Nutrition Society of Malaysia, 2024)
Indexed by SCOPUS/MYCITE